PENGEMBANGAN EDU-ECOTOURISM UNTUK MENDUKUNG WISATA EDUKATIF DAN KONSERVASI BERBASIS PEMBERDAYAAN KOMUNITAS LOKAL DI WILAYAH PENYANGGA IBU KOTA NUSANTARA, KALIMANTAN TIMUR - Eni Muryani; Aditya Pandu Wicaksono; Stefani Dian Setyawati; Luthfi Qurrotu’ Aini Nurshodik; Andini Shafa Saraswati Saraswati (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The development of Indonesia’s new capital city (IKN) in East Kalimantan requires sustainable management of its surrounding buffer areas to maintain ecological, social, and economic balance. These buffer zones possess significant potential for the development of edu-ecotourism based on biodiversity, forest and coastal ecosystems, and local wisdom. This community service program aims to strengthen local community capacity in developing edu-ecotourism as a tool for educational tourism and environmental conservation. A participatory approach was applied through socialization activities, focus group discussions, planning assistance, and the strengthening of multi-stakeholder collaboration involving local communities, regional governments, academics, and related partners. The activities were conducted in several buffer area districts of Kutai Kartanegara Regency and Penajam Paser Utara Regency. The results indicate an increase in community understanding of edu-ecotourism concepts, the formulation of educational tourism package ideas based on local potential, and the establishment of multi-stakeholder synergy to support sustainable tourism management. Community-based edu-ecotourism development is therefore a relevant strategy to support the sustainability of educational tourism destinations while enhancing community participation in natural resource conservation within the IKN buffer areas. Keywords: cedu-ecotourism, IKN buffer area, community empowerment, environmental conservation